2015
DOI: 10.1128/jvi.02500-14
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-Zoster Virus-Derived Major Histocompatibility Complex Class I-Restricted Peptide Affinity Is a Determining Factor in the HLA Risk Profile for the Development of Postherpetic Neuralgia

Abstract: Postherpetic neuralgia (PHN) is the most common complication of herpes zoster and is typified by a lingering pain that can last months or years after the characteristic herpes zoster rash disappears. It is well known that there are risk factors for the development of PHN, such as its association with certain HLA alleles. In this study, previous HLA genotyping results were collected and subjected to a meta-analysis with increased statistical power. This work shows that the alleles HLA-A*33 and HLA-B*44 are sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Associations of HLA alleles with PHN in Japanese have been reported in three independent studies . Meysman et al recently performed a meta‐analysis of these Japanese studies and compared the HLA frequencies in PHN patients with those in HZ patients without developing PHN and controls . Significant changes in PHN patients either in the meta‐analysis data of Japanese or in the present study of Koreans are shown in Table .…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Associations of HLA alleles with PHN in Japanese have been reported in three independent studies . Meysman et al recently performed a meta‐analysis of these Japanese studies and compared the HLA frequencies in PHN patients with those in HZ patients without developing PHN and controls . Significant changes in PHN patients either in the meta‐analysis data of Japanese or in the present study of Koreans are shown in Table .…”
Section: Discussionsupporting
confidence: 49%
“…Association of HLA alleles with PHN may be explained from another view point in that differences in varicella‐zoster virus peptide binding affinity of different HLA molecules may confer susceptibility or protection to the development of PHN in HZ patients. In this context, Meysman et al performed prediction of the virus peptide affinity for four different HLA alleles after the aforementioned meta‐analysis of the Japanese studies . They chose HLA‐A*02 and B*40 (both depleted in PHN) and A*33 and B*44 alleles (both enriched in PHN) as candidate alleles conferring protection and susceptibility to the development of PHN, respectively (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Although our IBM has given us valuable insights into between-host and within-host VZV dynamics, other influential factors could be introduced in future versions. These factors could relate to CMV-immunosenescence ( Ogunjimi et al, 2014 ), maternal antibodies, reduced VZV-CMI induction if infected during the first year of life as this might improve the prediction of the teenage group ( Terada et al, 1994 ), co-infection with other viruses ( Ogunjimi et al, 2015 ), risk groups (for e.g., immunosuppressed individuals) and HLA types ( Meysman et al, 2015 ). Although current deterministic compartmental models should be able to partially account for these effects, a VZV IBM seems better suited to directly model the influence of these immunity-perturbing factors.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In addition, certain HLA types have been shown to be enriched in individuals with prolonged HZ (post-herpetic neuralgia). 7 Cytomegalovirus (CMV), another human herpesvirus (HHV) with latency-reactivation cycles, is well known for its modulating effects on immunity. For e.g., VZV-specific T-cells, but also T-cells against other HHV, from CMV-seropositive individuals are more mature, further differentiated and thus possibly less responsive compared to the VZV-specific T-cells from CMVseronegative individuals.…”
Section: Introductionmentioning
confidence: 99%